(3JGQjN OGQjGs - (3YHO GdLHGQ Hf YHO Gddg Hf eMeO Hf YHO GdQMje CHj Ydj GdNhdGfj GdOGQGfj,J (B370 (3g` s
(3ChdgG (B:s
(3PcQ ef fRd OGQjG ef CUMGH QShd Gddg (B((3U(B) s
(3BNQgG (B:s
(3GdMeO ddg QH GdYGdejf hUdhGJg Ydi NjQ Ndbg eMeO hBdg hUMHg hSde s
(3OGQjG bQjI cHjQI eTghQI ef bQi OeTb HGdZhWIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B275s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B11 - (3U (B60 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(3616) s
Keywords: (3GdJGQjNs